Landscape Design: Aesthetic Characteristics of Plants - Gail Hansen; Erin Alvarez (EDIS)
ENH1172, an 8-page illustrated fact sheet by Gail Hansen and Erin Alvarez, discusses form, texture, size, and color of landscape plants and how to choose plant combinations based on these qualities to create a composition of plant material. Includes references. Published by the UF Department of Environmental Horticulture, September 2010.